Telling Story! Voice in Photography: An online visual art critical studies program evaluation - Sandra Semchuk (Athabasca University Press, 2004)
This article highlights the current dialogue about educational technology and ways of knowing in visual art education. The authors outline and evaluate the development and testing phases of a hypertextual online visual art course offered at the then Emily Carr Institute of Art and Design (http://www.eciad.ca/www/) in the summer of 2001. Through this, we offer a framework for the evaluation of online visual art critical studies courses.